The COVID-19 Pandemic Fear and Psychological Status of the Medical Students of a Private Medical College in Bangladesh - Khan, Farzana Islam; Sayef, Shefat Ahmed; Billah, Syed Muhammad Baqui (International Journal of Human and Health Sciences (IJHHS), 2025)
Background: The uprising of the COVID-19 pandemic has disrupted educational systems, posing psychological challenges, particularly for medical students, who faced heightened academic and health-related stress. Objectives: The study explored the relationship of medical students’ mental health outcomes and their fear of the COVID-19 pandemic. It also examined how demographic and situational factors affect depression, anxiety, and stress levels. Methods: This cross-sectional, descriptive study was conducted among 240 medical students of Ashiyan Medical College, a private medical college in Dhaka, Bangladesh, between January and August of 2022. We used a self-administered questionnaire for data collection. The Fear of COVID-19 Scale (FCV-19S) was the independent variable, while the Depression, Anxiety and Stress Scale (DASS-21) was the dependent variable as a measure of psychological effect, with other related socio-demographic factors. Results: FCV-19S showed significantly positive correlations with all mental health subscales. Female students exhibited significantly higher levels of stress (p<0.001) and fear (p<0.001) compared to their male counterparts. Students not living with their families had elevated fear and depression scores. Those, whose lives were severely affected by the COVID-19, demonstrated the highest levels of fear, depression, anxiety, and stress. Conclusion: Poor mental health outcomes were highly correlated with fear of the COVID-19 pandemic among medical students in Bangladesh. The finding underscores for planned and targeted psychological support to combat such emergencies in future. International Journal of Human and Health Sciences Vol. 09 No. 04 Oct’25 Page: 223-230